The Impact and Difference of Laboratory Use on Student Learning Outcomes - Muliandi, arief; Tarmizi, Tarmizi; Hamid, Abdul (Universitas Syiah Kuala, 2019)
Laboratories are an important part of physics learning activities in schools. However, learning activities in MAN 3 Banda Aceh still rarely use laboratory facilities. It is important to do research related to the use of laboratories in physics lessons. This study aims to determine the impact of laboratory use in achieving physics learning outcomes in MAN 3 Banda Aceh. This study uses a quantitative approach with the method used, namely the experimental method by comparing between experimental classes taught using laboratories and control classes that are not taught to use laboratories after being treated. The population in this study were all students of class X MIA in MAN 3 Banda Aceh. The research sample was selected by purposive sampling, which consisted of class X MIA 1 as the experimental class and class X MIA 2 as the control class. The research data consisted of pre-test and post-test. Then the data of this study were analyzed using t-test statistics. Results The study found that the pre-test value was normally distributed and homogeneous. Then based on the t-test obtained, (4.118) (2.009). It can be concluded that the results of physics learning using laboratories are better than those that do not use laboratories in students of MAN 3 Banda Aceh.